The Value-Added Contribution of Exercise Commitment to College Students’ Exercise Behavior: Application of Extended Model of Theory of Planned Behavior - Zhang, Wen-Juan; Xu, Menglin; Feng, Yu-Juan; Mao, Zhi-Xiong; Yan, Zeng-Yin; Fan, Teng-Fei (Frontiers in Psychology, 2022)
Abstract: The aim of this study was to investigate the applicability of the planned behavior theory model (TPB-5) and TPB-6 model of enhanced physical exercise in college students, and to explore the role of exercise commitment in the relationship between exercise intention and behavior, so as to provide theoretical and empirical support for college students to promotion exercise. The study participants were 581 college students ( male = 243, female = 338, age = 19. 27±0. 94) are investigated with Theory of Planned Behavior Scale, Exercise Commitment Scale and Physical Activity Rating Scale. Results showed that the explanatory power of the theory of planned behavior to exercise intention and exercise behavior is 0.70 and 0.52 respectively, and exercise intention was the primary factor to predict exercise behavior of college students. The Model fit of TPB-6 model is acceptable, compared with TPB 5-factor model, the predictive power of TPB-6 (with the mediator: exercise commitment) on behavioral intention increases from 70.0% to 75.0%, and the predictive power towards behavior raises from 52.0% to 59.0%. exercise commitment has a partial mediating effect between exercise intention and behavior, which accounts for 26.89% of the total effect, but it has no moderating effect. In conclusion, this research demonstrates the TPB-5 model has good applicability among college students, with exercise commitment variables, exercise intention can better predict college students' exercise behavior, which can be used as the theoretical basis for the intervention on their exercise behavior.